Exploring healthcare providers’ perspectives on the factors that facilitate primary health care access among Aboriginal and Torres Strait Islander young people: a qualitative study in Southeast Queensland - Stephen Harfield; Judith A. Dean; Peter Azzopardi; Gita D. Mishra; James Ward (BMC Primary Care)
Abstract Background Aboriginal and Torres Strait Islander young people aged 15–24 years of age often encounter challenges accessing and utilising primary health care (PHC). Providing health care responsive to the needs of Aboriginal and Torres Strait Islander young people requires the active involvement of healthcare providers (HCPs), who play a central role in healthcare delivery. This study explored perspectives of HCPs working in urban Aboriginal and Torres Strait Islander Community-Controlled Health Organisations (ATSICCHOs) on the factors that facilitate Aboriginal and Torres Strait young people accessing and utilising PHC services. Methods Thirteen research yarns were conducted with HCPs in urban southeast Queensland (SEQ), Australia. Inductive thematic analysis was used to identify factors facilitating health care access and utilisation and were mapped to a social-ecological framework model. Results Three overarching strength-based themes that facilitate access to health care were common across research yarns: (1) The ATSICCHO model of care addresses the needs of Aboriginal and Torres Strait Islander young people; (2) Family and community play a key role in facilitating Aboriginal and Torres Strait Islander young people’s access to healthcare services; and (3) The characteristics of Aboriginal and Torres Strait Islander young people that support health-seeking behaviour. Specific factors identified included targeted programs and initiatives specifically for Aboriginal and Torres Strait Islander young people; equitable access to holistic, comprehensive and culturally safe PHC; characteristics and skills of the ATSICCHO workforce that support young people’s engagement and access; and young people’s motivation to be healthy and to seek care. Barriers contrasting these themes were also identified. Conclusion HCPs from urban ATSICCHOs provide a unique perspective on the healthcare experience of Aboriginal and Torres Strait Islander young people and the factors that facilitate and/or challenge their access to PHC services. Improving PHC access among Aboriginal and Torres Strait Islander young people should focus on multilevel strategies across all three levels of the social-ecological model, with a particular focus on increasing opportunities for equitable access to PHC services for young people, enhancing target programs and initiatives for young people, and supporting the knowledge, skills and capacity of HCPs to delivery appropriate, culturally safe and holistic care.